DNA extraction from musa sp. using conventional method / Nur Syazni Sulaiman - Sulaiman, Nur Syazni (2017)
In Malaysia, banana is the second most widely cultivated fruit and about 12% of the total production is exported. Apart from being consumed as a fresh fruit, Musa sp. leaves are used worldwide as cooking material, natural herbs for skin, cosmetic and medicinal used. Extracting DNA mature leaves from plant sample is not an easy approach. The aim of this study is to identify the best conventional method and to compare the concentration and purity of DNA produced by extracting plant DNA from Musa sp. Three conventional methods are being used in this study; CTAB buffer method, SDS buffer method and Phenol Chloroform Isoamyl alcohol method. In addition, further study of CTAB buffer method is being done by altering the incubation time of the sample. Results obtained indicate that CTAB buffer method is the best method among all that being study with the ideal incubation time of forty five minutes. CTAB buffer method shows 1.541 of DNA purity compare to SDS buffer method which is 1.292 and Phenol Chloroform Isoamyl with 0.077. Therefore, in extracting mature Musa sp. leaves, the best method to be done is by using CTAB method with incubation time of forty five minutes at 65°C.